2013
DOI: 10.1002/smi.2556
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐wave Study of Antecedents of Work–Family Enrichment: The Roles of Social Resources and Affect

Abstract: On the basis of conservation of resources theory (Hobfoll, ) and the resource-gain-development perspective (Wayne, Grzywacz, Carlson, & Kacmar, ), this paper examines the differential impact of specific social resources (supervisory support and family support) on specific types of affect (job satisfaction and family satisfaction, respectively), which, in turn, influence work-to-family enrichment and family-to-work enrichment, respectively. A sample of 276 Chinese workers completed questionnaires in a three-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 53 publications
2
61
0
4
Order By: Relevance
“…By definition, flexibility i‐deals are individualized to employees' unique work needs and are differentiated from what others already have; hence, recipients of flexibility i‐deals are likely to feel valued and happy, which positively affects their functioning in the family domain (Bakker & Demerouti, ). This is supported, for example, by a study by Siu et al () showing enrichment between work and family domains, which demonstrates that work resources (e.g., supervisor support) relate positively to work‐to‐family enrichment. Similarly, Daniel and Sonnentag () show that work resources (i.e., work engagement) relate to work‐to‐life enrichment, having an impact beyond the family, through instrumental and affective pathways, as suggested by the interrole enrichment perspective.…”
Section: Hypothesis Developmentmentioning
confidence: 57%
See 2 more Smart Citations
“…By definition, flexibility i‐deals are individualized to employees' unique work needs and are differentiated from what others already have; hence, recipients of flexibility i‐deals are likely to feel valued and happy, which positively affects their functioning in the family domain (Bakker & Demerouti, ). This is supported, for example, by a study by Siu et al () showing enrichment between work and family domains, which demonstrates that work resources (e.g., supervisor support) relate positively to work‐to‐family enrichment. Similarly, Daniel and Sonnentag () show that work resources (i.e., work engagement) relate to work‐to‐life enrichment, having an impact beyond the family, through instrumental and affective pathways, as suggested by the interrole enrichment perspective.…”
Section: Hypothesis Developmentmentioning
confidence: 57%
“…. This is supported, for example, by a study by Siu et al (2015) showing enrichment between work and family domains, which demonstrates that work resources (e.g., supervisor support) relate positively to work-to-family enrichment.…”
Section: Cor Theory and The W-hr Model In Relation To I-dealsmentioning
confidence: 68%
See 1 more Smart Citation
“…It has considerable breadth and has been applied to many contexts, particularly the occupational context and the nexus between stress and health (e.g. Boyd, Tuckey, & Winefield, ; Gao, Shi, Niu, & Wang, ; Jenkins, Heneghan, Bailey, & Barber, ; Siu et al, ; Zijlstra, Cropley, & Rydstedt, ). The strength or resource‐depletion model is a dominant model of self‐control and suggests that individuals' capability to regulate the self is finite and dependent on a form of strength or ‘energy’ (Baumeister et al, ; Muraven, Tice, & Baumeister, ).…”
mentioning
confidence: 99%
“…For example, Tang et al (2014) found that supervisory support and organizational support are important antecedent of work-to-family enrichment. Siu et al (2013) found that family support is an important role resource for family-to-work enrichment. Therefore, this conceptual paper presents the following proposition:…”
Section: Chinese Family Orientationmentioning
confidence: 99%